Advanced modeling of seepage dynamics and control strategies in thick coal seams under high-confined aquifer conditions: A case study - Xuyang Chen; Xufeng Wang; Dongsheng Zhang; Liang Chen; Jiyao Wang; Zechao Chang; Dongdong Qin; Hao Lv (Alexandria Engineering Journal)
The hydraulic behavior of the connection between the floor failure area and the aquifer water-conductive zone is considered to be the root cause of mine water inrush disasters. Therefore, unraveling the floor failure mechanism is particularly important for safe coal mining above the high-confined aquifer. This paper estimates the depth of the baseplate failure to be 18.4–27.3 m by combining network parallel electrical methods with drilling visualization technology. The FLAC3D-based numerical model considering the strain hardening of caved rock was established with rigorous calibration and verification. The results showed that the depth of damage to the floor is 23.1 m, and the dominating floor failure mechanism is shear failure caused by the vertical stress exceeding the rock bearing capacity. Moreover, the stress recovery process of the baseplate does not alter the failure morphology of the baseplate. Based on the above research findings, the in-situ floor control technique of the working face No. 4305 is proposed and practiced in the field. Field measurements show that floor control performance is satisfactory with water inflow in the goaf being roughly stable at 50 m3/h. Our results can provide useful reference for safe mining above confined aquifer and prevention and mitigation of water-related hazards.